UPAYA MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN MELALUI METODE IQRO’ PADA SANTRI KELAS 3 TPQ DI MADRASAH NURUL HUDA - Dinda Alifatur Rodziah; Royanatul Jannah; Lutfiatuz Zahro (PT. Sulthan Journal Publisher, 2026)
This study aimed to improve the Qur’an reading ability of Grade 3 TPQ students at Madrasah Nurul Huda through the implementation of the Iqro’ method. The study employed a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 12 students who were studying Iqro’ levels 5–6. Data were collected through Qur’an reading ability tests, classroom observations during the learning process, and documentation as supporting data. The results showed that the implementation of the Iqro’ method significantly improved the students’ Qur’an reading ability. In the pre-cycle stage, the learning mastery level reached only 33.3%, which increased to 83.3% in Cycle I and reached 100% in Cycle II. The improvement was reflected in the students’ fluency in reading, accuracy in pronouncing the Arabic letters according to their proper articulation points (makharijul huruf), and their ability to distinguish between long and short recitations. In addition, the students demonstrated greater self-confidence and participation during the learning process. Based on these findings, it can be concluded that the Iqro’ method is effective in improving the Qur’an reading ability of Grade 3 TPQ students at Madrasah Nurul Huda.